Ecotourism Development of Phu Quoc Island Under Resource-Based View Approach - Huy, Hoang Pham; Khin, Aye Aye (International Journal of Economics and Financial Issues, 2016)
Currently, eco-tourism has emerged as a debatable argument in a large number of forums and discussion in the tourism industry. Eco-tourism is defined by the International Eco-tourism Society as “responsible travel to natural areas that conserves the environment and improves the well being of local people”. Phu Quoc Island in Vietnam can be taken as a typical example of eco-tourism. If eco-tourism is successfully developed, it can make not only the best use of Phu Quoc’s environmental and economic, but also diminish any harm to the environment of this island. However, any resolutions to promote eco-tourism development of Phu Quoc Island by creating stable competitive advantages were poorly conducted. As a result, this study found that if it would be used the Resourced-Based View approach to propose solution packages of advancing the sustainable competitive advantage of Phu Quoc island, it would be in order to boost the development of eco-tourism. Keywords: Ecotourism, RBV, Sustainable Competitive Advantage JEL Classifications: M20, M31, Z33